Aliskiren Attenuates the Inflammatory Response and Wound Healing Process in Diabetic Mice With Periodontal Disease - Oliveira, Sandra Helena Penha; Brito, Victor Gustavo Balera; Frasnelli, Sabrina Cruz Tfaile; Ribeiro, Bianca da Silva; Ferreira, Milena Nunes; Queiroz, Dayane Priscilla; Beltan, Carluci Taís; Lara, Vanessa Soares; Santos, Carlos Ferreira (Frontiers in Pharmacology, 2019)
The aim of this study was to characterize the role of local RAS in the inflammatory response of normal (N) and diabetic (D) mice with periodontal disease (PD). DM was induced by peritoneal injection of streptozotocin in Balb/c mice. PD was induced in both N and D, irrespective of whether they were treated with Aliskiren (Alisk). Mandibles were harvested for histomorphometric analyses and gingival tissue (GT) was collected to evaluate gene expression and extracellular matrix components (ECM). Immunohistochemical analyses (IHC) were used to localize RAS in GT. The production of C-reactive protein (CRP), IL-1β, CXCL2, and CCL8 were evaluated by ELISA. Renin was found to exacerbate the inflammation and periodontal bone loss at 14 days after PD, and Alisk inhibited this process in GT of N and D. PD enhanced expression and production of AGT, ACE, AT1R, and AT2R in both N and D. AT1R expression was higher in D with PD and AT2R expression was higher in N with PD. ACE2 and receptor Mas (MasR) expression and production was elevated in the control group of both animals. PD inhibited ACE2 in N but not in D. MasR expression was unaffected in both N and D with PD. Alisk reduced expression and production of all RAS components in GT of both animals, except for ACE2 in N. RAS staining was observed in all layers of epithelium, basal cell layer and lamina propria. PD increased CRP, CXCL2, and CCL8 production in both animals, and Alisk could inhibit them primarily in D animals. However, only CCL8 was decreased in N animals after Alisk pretreatment. Col1a1, Col1a2, Col3a1, and fibronectin (Fn1) were increased in both animals with PD. Alisk inhibited Col1a1 and Fn in both animals, Col1a2 was decreased only in D, while levels of Col3a1 remained unchanged in all animal groups. In conclusion, these data demonstrated the presence and functional role of local RAS in GT, exacerbating the inflammatory response, periodontal bone loss, and wound healing processes in both N and D animal groups. In addition, Alisk was able to significantly reduce gingival inflammation, excessive wound healing processes, and periodontal bone loss.